DHIKR THERAPY IN THE TREATMENT OF ANXIETY DISORDERS IN ADOLESCENTS - Maslahat, Meta Malihatul; Laila, Vina Noor (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
ABSTRACT This study aims to determine the role of dhikr therapy in reducing anxiety disorders in adolescents at the Maunatul Mubarok Sayung Demak Social Rehabilitation Center for Mental Illness and Drugs. The research method used in this study is a qualitative method with the type of field research. The data obtained in this study is through observation, interviews and documentation. The results of this study indicate that dhikr therapy plays a role in reducing anxiety disorders in adolescents at the Maunatul Mubarok Sayung Demak Social Rehabilitation Center for Mental Illness and Drugs. Through dhikr therapy, adolescents who experience anxiety disorders begin to show better life changes, including feeling calmer in spirit, feeling motivated to continue to improve themselves, seeing themselves more positively and also being more confident. The factors that influence the effectiveness of this dhikr therapy are internal and external influences. Internal influence is a strong motivation within oneself to change towards a better life. While external influences are encouragement from therapists and those closest to them to always guide and remind patients to always remember Allah in every situation, because only by remembering Allah will the soul become calm.